Impact of Different Drying Methods on Magnolia officinalis Leaves - Lan, Xue-Mei; Yang, Xiao-Hong; Li, Jia-qi; Xue, Zhen-zhen; Yang, Rong-Ping; Li, Hua; Yang, Bin (Planta Medica, 2025)
Different drying techniques can affect the quality characteristics of Magnolia officinalis leaves (MOLs), including their chemical composition, color, and biological activity. This study comprehensively evaluated five drying methods: vacuum drying (VD), hot-air drying (HAD), freeze drying (FD), sun drying (SD), and shade drying (SHD). The non-volatile and volatile constituents of MOLs were analyzed by high-performance liquid chromatography (HPLC) and gas chromatography–mass spectrometry (GC-MS), respectively. Objective color parameters were measured using an electronic eye, and the antioxidant activity was evaluated by the DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging assay. Additionally, the moisture content and the alcohol-soluble extract content were determined. Results indicated that HAD had the least impact on the color, chemical composition, and antioxidant activity of MOLs, thereby demonstrating its superiority over the other four drying methods.
Keywords: Magnoliaceae; Magnolia officinalis leaves; drying method; chemical composition; antioxidant activity color